Lukan authorship of Hebrews - Allen, David Lewis, 1957- (Nashville, Tenn. : B&H Academic, 2010)
Lukan Authorship of Hebrews explains why Luke is the likely author of the book of Hebrews. The ramifications of this possibility are then detailed in depth, including the way Hebrews informs the interpretation of the books of Luke and Acts. Also present throughout is analysis of the writing style similarities between Hebrews, Luke, and Acts. --from publisher description.
Historical survey of the authorship question: development of the Lukan theory -- Barnabas, Apollos, Paul -- The linguistic argument: lexical, stylistic, and textlinguistic evidence -- The purposes of Luke: Acts and Hebrews compared -- The theology of Luke: Acts and Hebrews compared -- The identity of Luke and the Jewish background of Luke-Acts -- Historical construction: Lukan authorship of Hebrews.
Based on the author's thesis (Ph. D.)--University of Texas, Arlington, 1987.
Includes bibliographical references (p. [380]-389) and indexes.
Keywords: Luke, -- Saint; Bible. -- Authorship; Bible. -- Criticism, interpretation, etc